Thinking infrastructures - Kornberger, Martin; Bowker, Geoffrey C.; Elyachar, Julia; Mennicken, Andrea; Miller, Peter; Nucho, Joanne Randa; Pollock, Neil (Emerald Publishing Limited, 2019)
This volume introduces the notion of Thinking Infrastructures to explore a broad range of phenomena that structure attention, shape decision-making, and guide cognition: Thinking Infrastructures configure entities (via tracing, tagging), organise knowledge (via search engines), sort things out (via rankings and ratings), govern markets (via calculative practices, including algorithms), and configure preferences (via valuations such as recommender systems). Thus, Thinking Infrastructures, we collectively claim in this volume, inform and shape distributed and embodied cognition, including collective reasoning, structuring of attention and orchestration of decision-making.
Includes index.
Keywords: Knowledge management.; Decision making.; Business & Economics, Infrastructure.; Sociology: work & labour.; elektronické knihy; electronic books